A percepção das características da face infantil por adultos e crianças sob uma perspectiva evolucionista - Souza, Catiane Kariny Dantas (2012)
Child facial cues evoke attention, parental care behaviors and modulate for infant- caretaker interactions. Lorenz described the baby schema ( Kindchenschema ) as a set of infantile physical features such as the large head, round face, high and protruding forehead, big eyes, chubby cheeks, small nose and mouth. Previous work on this fundamental concept was restricted to positive perception to infant face, and did not show consistent results about the development individuals perceptions, regarding the physical attributes that worked as markers of cuteness. Here, we experimentally tested the effects of baby schema on the perception of cuteness of infant faces by children and adults. We used 60 none graphically manipulated photos of different stimulus children faces from 4 to 9 years old. In the first task for the adults experimental subjects, ten stimulus photos were shown, whereas for children experimental subjects, four stimulus photos were shown at a time, with a total of six rounds. The second task involved only adults, who indicated the motivation of affective behaviors and care directed to children through a Likert scale. Our results suggest that both participants judged similarly the cuteness of children's faces, and the physical features markers of this perception were observed only for younger stimulus children. Adults have attributed more motivations of positive behaviors to cuter stimulus children. The recognition of the baby schema by individuals of different ages and genders confers the universality and power of children's physical attributes. From the evolutionary perspective the responsiveness to baby schema is significant to ensure aloparental and parental investment, and the consequent children survival